A low cost multi-touch surface - Chng, Eric Boon Keat. (2010)
Multi-touch is a human-computer interaction technique that was popularized by Apple’s iPhones. Its intuitiveness provides mass appeal, and its applications range from games to desktop management and even specialized areas such as medical visualization. However, commercial multi-touch solutions, such as the Microsoft Surface, are often too expensive for individuals and small organizations.